ADVANCES IN FABRICATION TECHNIQUES OF EPITAXIAL SILICON P-N STRUCTURES FOR THERMOELECTRIC APPLICATIONS - F. Arzikulov; Sh. Kuchkanov (American Journals Publishing, 2024)
This article explores recent advances in fabrication techniques for silicon-based epitaxial p-n junctions, focusing on the role of molecular beam epitaxy (MBE), chemical vapor deposition (CVD), and atomic layer deposition (ALD). These techniques allow for precise control of doping concentrations, layer thicknesses, and interface quality, leading to improved thermoelectric efficiency. Additionally, the article discusses the challenges of minimizing thermal conductivity while maximizing electrical conductivity, aiming to optimize the thermoelectric figure of merit (ZT).
Keywords: Epitaxial silicon, p-n junction, thermoelectric applications, molecular beam epitaxy (MBE), chemical vapor deposition (CVD), atomic layer deposition (ALD), ion-stimulated vacuum deposition (ISVD), ion treatment, energy harvesting, waste heat recovery.